Breast Cancer Screening Beliefs Questionnaire: Psychometric properties assessment of the Arabic version. (February 2016) - Kwok, Cannas; Endrawes, Gihane; Lee, Chun Fan
Abstract: Purpose: The aim of the study was to report the psychometric properties of the Arabic version of the Breast Cancer Screening Beliefs Questionnaire (BCSBQ). Methods: A convenience sample of 251 Arabic-Australian women was recruited from a number of Arabic community organizations. Construct validity was examined by Cuzick's non-parametric test while Cronbach α was used to assess internal consistency reliability. Explanatory factor analysis was conducted to study the factor structure. Results: The results indicated that the Arabic version of the BCSBQ had satisfactory validity and internal consistency. The Cronbach's alpha of the three subscales ranged between 0.810 and 0.93. The frequency of breast cancer screening practices (breast awareness, clinical breast-examination and mammography) were significantly associated with attitudes towards general health check-up and perceived barriers to mammographic screening. Exploratory factor analysis showed a similar fit for the hypothesized three-factor structure with our data set. Conclusions: The Arabic version of the BCBSQ is a culturally appropriate, valid and reliable instrument for assessing the beliefs, knowledge and attitudes to breast cancer and breast cancer screening practices among Arabic-Australian women. Highlights: Arabic-Australian (AA) women appear having low breast cancer screening practices. Valid and reliable instrument is essential to understand factors that influence AA women's cancer screening behaviours. The Arabic version of the BCSBQ is a valid and reliable instrument for exploring cancer screening behaviours among AA women.